Heterogeneous Co-catalyzed direct 2-alkylation of azoles with ethers. Issue 25 (12th April 2018) - Yang, Ke; Li, Dashan; Zhang, Lei; Chen, Qun; Tang, Tiandi
Abstract : The direct 2-alkylation of oxazoles and thiazoles with ethers through cross-dehydrogenative coupling reaction using Co-containing mesoporous zeolite ETS-10 as the heterogeneous catalyst is described. Abstract : The direct 2-alkylation of oxazoles and thiazoles with ethers through cross-dehydrogenative coupling reaction using Co-containing mesoporous zeolite ETS-10 as the heterogeneous catalyst is described. The basic Co-containing mesoporous zeolite ETS-10 catalyst facilitates this cross-dehydrogenative coupling reaction through metal-base synergy catalytic principle.